PERENCANAAN TATA RUANG TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN SWASTA KOTA PALEMBANG - Cahyani, Eni (Universitas Muhammadiyah Palembang, 2016)
Purpose - This study aims to determine the effect on employee performance spatial planning.Design/methodology - The analysis conducted on four private company covers 30-500 samples are employees of private companies in the city of Palembang. Testing the hypothesis in this study will be conducted using Structural Equation Model (SEM).Findings – The results showed that the performance can be explained by the variable furniture and the preparation of the physical environment. The individual test results showed that there are two variables : the preparation of the furniture and the physical environment positive effect on performance.